Application arbuscular mycorrhizal fungi Glomus sp. and Trichoderma sp. as biofertilizer and biostimulator of tomatoes growth (Solanum lycopersicum L.) - Anggiani, Anak Agung Yulia; Proborini, Meitini Wahyuni; Muksin, I Ketut; Narayani, Inna (Jurnal Biologi Udayana; Vol 25 No 2 (2021): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2021.v25.i02.p02, 2021)
Tomato ( Solanum lycopersicum L.) is a horticultural crop that has many benefits and potential to be developed. Market demand for tomatoes is increasing, but tomato production in Bali has decreased due to biotic and abiotic factors. One of efforts to increase tomato production is by using the Mycorrhizal Arbuscular Fungi (FMA) Glomus sp. and Trichoderma sp. which act as a biofertilizer and biostimulator. The study was conducted in November 2020 until February 2021 and aims to analyze the effect of AMF, Trichoderma , and combinations on the growth of tomato plants. Research site was at the Greenhouse and the Laboratory of Plant Taxonomy in the Department of Biology Faculty of Mathematics and Natural Sciences Udayana University. The experiment used factorial Randomized Block Design (RBD) with two factors, three replicates. First factor was the dose of AMF Glomus (0, 100, 150, and 200 spores per plant) and the second factor was the dose of Trichoderma (0, 10, and 20 mL per plant). Data of this study was analyzed using Analysis of Variance (ANOVA) followed by Duncan Multiple Range Test (DMRT). The result showed that AMF Glomus 150 spores increased plant height, root length, number of flower bunches, dry plant mass, and obtained the highest AMF colonization percentage at 35% (medium category).